2022
DOI: 10.1109/tcad.2021.3136982
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimentation of Inductorless Low-Pass NGD Integrated Circuit in 180-nm CMOS Technology

Abstract: This paper introduces an innovative design of a low-pass (LP) negative group delay (NGD) integrated circuit (IC) in 180-nm CMOS technology. The LP-NGD circuit is an inductorless topology constituted by RC-network with CMOS metal-insulator-metal (MIM) capacitor and poly gate resistor. The design methodology is illustrated by considering the chip layout process. Then, the first run simulation is performed with the design rule check (DRC) and 2.5 mm × 2.2 mm layout versus schematic (LVS) approaches. The feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…The technical challenge slowing down the development of constant phase BP-NGD PS is the integration feasibility in miniaturized Tx-Rx system. The prominent solution is the design in CMOS integrated circuit (IC) technology whose the feasibility for LP- [41][42] and HP- [43] NGD circuits were 1 recently theoretically investigated.…”
Section: B State Of the Art On The Ngd Circuit-based Phase Shifter (P...mentioning
confidence: 99%
See 2 more Smart Citations
“…The technical challenge slowing down the development of constant phase BP-NGD PS is the integration feasibility in miniaturized Tx-Rx system. The prominent solution is the design in CMOS integrated circuit (IC) technology whose the feasibility for LP- [41][42] and HP- [43] NGD circuits were 1 recently theoretically investigated.…”
Section: B State Of the Art On The Ngd Circuit-based Phase Shifter (P...mentioning
confidence: 99%
“…[41][42][43], the proposed BP-NGD PS one should start from the targeted specifications to the final layout design. The main actions behind the design methodology of BP-NGD PS ICs are indicated by the design flow depicted by Fig.11.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In difference with the filter theory which is based on the magnitude frequency response, the NGD theory depends on the group delay (GD) diagram [1][2][3][4]. The types of low-pass (LP) [5][6][7][8][9][10][11][12][13][14][15][16][17], high-pass (HP) [18][19][20][21][22][23], bandpass (BP) [24][25][26][27], stop-band (SB) [28][29] and all-pass (AP) [30] NGD circuit topologies were introduced with R, L and C lumped components. Somehow, one may confuse NGD and filter behaviors.…”
Section: Fundamental Definitions and Types Of Ngd Circuitsmentioning
confidence: 99%
“…Some decades ago, particular engineering and scientific work efforts were paid on the development of the negative group delay (NGD) electronic circuit design with remarkable research results . Indeed, it was outstandingly theoretically and experimentally demonstrated that the NGD circuits present a strange property of generating outputs in advance of its input [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some of curious interpretations want to state that the NGD effect is like an impossible phenomenon or also classified as anomalous physical phenomenon.…”
Section: Introductionmentioning
confidence: 99%